2013
DOI: 10.3109/1040841x.2013.794127
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of viable but nonculturable state research: Unsolved molecular mechanisms

Abstract: Viable but nonculturable (VBNC) cells were recognized 30 years ago; and despite decades of research on the topic, most results are disperse and apparently incongruous. Since its description, a huge controversy arose regarding the ecological significance of this state: is it a degradation process without real significance for bacterial life cycles or is it an adaptive strategy of bacteria to cope with stressful conditions? In order to solve the molecular mechanisms of VBNC state induction and resuscitation, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
235
1
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(254 citation statements)
references
References 134 publications
5
235
1
13
Order By: Relevance
“…When exposed to stressful conditions such as starvation and low temperatures, many species of bacteria can enter the VBNC state (Oliver, 2010;Pinto et al, 2015). It has been suggested that the VBNC state is an adaptive strategy for long-term survival of bacteria under unfavorable environmental conditions (Ducret et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to stressful conditions such as starvation and low temperatures, many species of bacteria can enter the VBNC state (Oliver, 2010;Pinto et al, 2015). It has been suggested that the VBNC state is an adaptive strategy for long-term survival of bacteria under unfavorable environmental conditions (Ducret et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A t least 68 species of bacteria have been shown to enter a state of dormancy in which cells are viable but nonculturable (VBNC) (1), allowing them to evade harmful environmental stresses while maintaining the ability to return to an active state when the stress is alleviated (2). These cells are viable, as evidenced by their intact cell membranes and continued gene expression; however, they fail to replicate on routine laboratory media (2,3).…”
mentioning
confidence: 99%
“…VBNC fenotyp, který je charakterizován neschopností buněk vytvářet kolonie na růstovém médiu, přestože jsou živé a udržují si metabolickou aktivitu, se vyskytuje u bakterií, které jsou vysoce adaptované na podmínky prostředí, v němž se vyskytují před přene-sením na standardní živnou půdu (Oliver, 2005). Existence fenomé-nu VBNC je známa již přes 30 let, mechanismy tohoto způsobu existence mikroorganismů však zdaleka nejsou objasněny (Pinto et al, 2015). Mezi druhy bakterií schopnými kazit pivo byl fenomén VBNC popsán u Lactobacillus acetotolerans, L. lindneri, L. paracollinoides a L. plantarum (Deng et al, 2014;Li et al, 2017;Liu et al, 2016;2017;Suzuki et al, 2004).…”
Section: Mikrobiologie Pivovarské Výroby -Bakterie Mléčného Kvašení Aunclassified
“…The VBNC phenotype occurs in bacteria that are highly adapted to environmental conditions in which they were prior to transfer to standard media (Oliver, 2005). The existence of VBNC phenomenon has been known for 30 years, but the life mechanisms of microorganisms in this state are not clarifi ed (Pinto et al, 2015). In a group of bacteria that degrade beer, VBNC phenomenon was described in Lactobacillus acetotolerans, L. lindneri, L. paracollinoides and L. plantarum (Deng et al, 2014;Li et al, 2017;Liu et al, 2016;2017;Suzuki et al, 2004).…”
Section: Složení a Příprava Kultivačních Médiímentioning
confidence: 99%